Analisis Faktor-Faktor Yang Mempengaruhi Alih Fungsi Lahan Sawah Menjadi Lahan Bukan Sawah Di Kabupaten Batu Bara - Simanjuntak, Ferry M; Akoeb, Erwin Nyak; Kardhinata, E. Harso; Syahbudin, Syahbudin (Universitas Medan Area, 2024)
This study aims to analyze several factors, including: farmers' income, the proportion of their own capital, the number of family workers and experience in lowland rice farming on land conversion from paddy fields to non-rice fields in Batu Bara Regency. This research was conducted in sub-districts that had converted the function of paddy fields to non-rice fields in Batu Bara Regency in 2019. The results showed that the net income of lowland rice farming was Rp. 25,220,635 per hectare per planting season or Rp. 18,102,972 per farmer per growing season. The ability of farmers to provide their own capital is 7,258,300 or 74.75% of the lowland rice farming capital. The number of workers in the family is 2.73 people per farmer, while the experience in rice farming is 13.33 years. The area of paddy fields belonging to farmers that has been converted into non-rice fields reaches 0.43 hectares from 0.72 hectares of paddy fields. The proportion of function conversion reached 62.58% of the farmers' rice fields. Partially, the factors that significantly affect the conversion of paddy fields to non-rice fields are the income of lowland rice farming, the proportion of own capital, the number of workers in the family that have a negative effect on land conversion, while the experience of farming lowland rice has no significant effect. Farmers will be encouraged to convert their land if their income and capital capacity are low, while workers in the family are also classified as lacking. Simultaneously the lowland rice farming income variables, the proportion of own capital, the number of family workers, and the experience of farming lowland rice have a significant effect on land conversion.